Cell wall-degrading enzymes and aggressiveness in Stagonopspora nodorum - Cui , K. R.; Krupinsky , J. M.; Dai , Q.; Arseniuk , E.; Ueng , P. P. (Plant Breeding and Seed Science, 2005)
Stagonospora nodorum produces cell wall degrading enzymes when grown in culture media containing cell wall components. The pathogen grew as well on minimal agar plates containing cellulose, xylan and pectin as glucose, except having sparser mycelia. Four cell wall-degrading enzymes, cellulase, xylanase, pectinase and b-1,3-glucanase were coordinately induced in culture filtrates growing on xyaln and cellulose as substrates. An aggressive isolate (sn26-1) secreted more cell wall-degrading enzymes than the others. Based on isoelectric focusing profiles, six to seven xylanase isozymes were induced by cellulose and xylan. No difference was found in the high (sn26-1) and low (9074) aggressive isolates. Addition of cell wall-degrading enzyme mixtures, not high xylanase alone, to a spore suspension of a low aggressive isolate (9074) caused a limited increase in tissue necrosis. We conclude that the cell wall degrading enzymes play a role in early penetration of the host by the fungus, but they are not important elicitors for disease development.